Coral community structure in Payar Island Marine Park, Malaysia - Khodzori, Fikri Akmal; Saad, Shahbudin; Mohammad Noor, Normawaty (Penerbit UMT, 2019)
Conservation efforts such as reef survey and monitoring programs are crucial to ensure the sustainable management of coral reef resources. The present study aims to investigate the diversity and abundance of corals at seven fringing reef sites in Payar Island Marine Park by applying a Coral Video Transect method. A total of 38 genera from 14 families of corals were identified. Massive Porites and massive-platy Physogyra were dominant in the coral assemblages cover almost 49% of the total live coral coverage. These corals have higher tolerance compared to other corals to withstand strong currents and high suspended sediment conditions. Reef sites in Payar Island were categorized as having ‘poor’ to ‘fair’ coral conditions with the percentages of live corals cover from 8.1% to 43.3%. The ‘poor’ average coral condition (15.7% ± 4.9) is most likely influenced by the impacts of sedimentation and uncontrolled tourism related activities. Current findings provide useful information on the current status of corals for a better reef management plan in Payar Island Marine Park.